Assessment of Gestational Diabetes Mellitus Among Primigravidas - Saleem, Fatima; Yasmin, Tahira; Awan, Fatima Rasul (Indus Journal of Bioscience Research, 2025)
Introduction: Gestational diabetes mellitus (GDM) is a notable metabolic disease among pregnant women which can have negative consequences on both the mother and baby. Understanding the GDM prevalence, as well as its complications, is vital for timely treatment and better health outcomes during and after birth. The present study seeks to determine the frequency of GDM and its association with different feto-maternal complications. Methodology: A descriptive case series study was performed on 121 pregnant women, classifying them by age, body mass index (BMI), gestational week, family history, socio-economic status, and any existing GDM. The prevalence of feto-maternal complications was documented, and their association to GDM was analyzed using statistical methods considering the level of significance at p<0.05. Results: GDM was present in 24.0% of cases. It showed significant associations with pre-eclampsia (p=0.001), preterm labor (p=0.001), macrosomia (p=0.001), intrauterine fetal death (p=0.047), respiratory distress (p=0.001), and NICU admission (p=0.015). No significant associations were found with age, gestational age, family history, or socio-economic status. Conclusion: Gestational diabetes mellitus (GDM) is strongly linked to adverse feto-maternal outcomes, highlighting the need for improved management and prevention. This study emphasizes proactive measures to reduce risks such as pre-eclampsia, preterm labor, macrosomia, and neonatal complications, ensuring better maternal and infant health through early intervention and optimized care strategies.